Effects of Sling Exercise on Flexibility, Balance Ability, Body Form, and Pain in Patients with Chronic Low Back Pain. Issue 6 (30th June 2016) - Park, Haejin; Jeong, Tchaewon; Lee, Junwoo
Abstract: Purpose: The aim of this study was to investigate the effects of sling exercise on pain, balance, flexibility, and body form in patients with chronic low back pain (LBP). Design: The pretest‐posttest control group design. Methods: Thirty participants with chronic lumbar pain were divided into three groups (Sling only, Sling+Swing stick flexible bar, and Sling+Ball cushion), and exercised for 12 weeks. Findings: All types of sling exercise provided significant positive effects on pain scale, body balance, flexibility, and body form. In particular, sling exercise with swing stick flexible bar or ball cushion was more effective on body form, flexibility, and balance than a sling alone. Conclusions: In conclusion, sling exercises over a period of 12 weeks had positive effects on flexibility, balance, pain, and body form in patients with chronic lumbar pain. Clinical Relevance: This study has generated effects of sling exercise, which will assist nursing practitioners in prescribing the beneficial physical rehabilitation for patients with chronic LBP.